Promoting Nuclear Security Education and Training Activities at Amity University, India - Arpita Datta; Dr. Alpana Goel (International Journal of Nuclear Security, 2020)
In the present era of global nuclear governance, it is the responsibility of every individual not only the security personals to be accountable for the security of nuclear materials, facilities and radioactive materials. Amity university and other universities of India are the largest educational networks for young professionals who will enter the nuclear programme in India and will be involved in the management of nuclear and other radioactive materials in a wide variety of applications such as hospitals, industrial applications and nuclear facilities. Amity University Uttar Pradesh is taking leading part to sensitize the importance of nuclear security amongst the students and faculty members of various Indian institutions and research organization. Amity University is also motivating women academicians to take lead in nuclear security. This paper describes details of various events organized in India with the initiative of INSEN, IAEA; Texas A&M University, USA and WINS Academy, Vienna, Austria.
Keywords: Nuclear security; Nuclear security awareness; Education; Training courses; PDCs; Workshop; Amity society.